2020
DOI: 10.1111/bjet.12999
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the focal points and sentiment of learners in MOOC reviews: A machine learning and SC‐LIWC‐based approach

Abstract: Despite the popularity of massive open online courses (MOOCs), only a small portion of the course participants successfully complete the course. The low completion rate can be partially attributed to the mismatch between the participants' expectations and value delivered by the courses. Therefore, this study leverages MOOC reviews to investigate the focal point and sentiment of the learners by combining machine learning techniques and statistical analysis. Several text mining methods (ie, simplified Chinese‐li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 54 publications
5
18
0
Order By: Relevance
“…Data mining and deep learning emphasize correlation judgments between samples and infer the population from the standard data set (Peral et al, 2017). What is more, researchers can apply data mining and deep learning to analyze objective behaviors and subjective perceptions of MOOC learners and instructors, make feature profiles of users, and propose personalized optimization schemes (Geng et al, 2020;Cagiltay et al, 2020…”
Section: Discussionmentioning
confidence: 99%
“…Data mining and deep learning emphasize correlation judgments between samples and infer the population from the standard data set (Peral et al, 2017). What is more, researchers can apply data mining and deep learning to analyze objective behaviors and subjective perceptions of MOOC learners and instructors, make feature profiles of users, and propose personalized optimization schemes (Geng et al, 2020;Cagiltay et al, 2020…”
Section: Discussionmentioning
confidence: 99%
“…The software program Linguistic Inquire Word Count (LIWC; Francis & Booth, 1993;Pennebaker et al, 2001), was used for the textual analysis. The LIWC has been translated in multiple languages (Meier et al, 2019;Zhao et al, 2016), used in different fields of study (Geng et al, 2020;Kidd & Castano, 2013;Pennebaker et al, 2014), and found to be a valid instrument (Bantum & Owen, 2009;Kahn et al, 2007).). The authors input the website descriptions of COVID-19 and telehealth into the program to derive statistical information about the text.…”
Section: Designmentioning
confidence: 99%
“…With the proliferation of online customer reviews, they now serve as an important and indispensable information source for a wide range of products and services. Online platforms, such as those for e-commerce [36], hotels [37], restaurants [38], touristic destinations [39], movies [40], and online education [6], commonly maintain an online review system for users to share their opinions. Online customer reviews play crucial roles in alleviating information asymmetry, reducing uncertainty, and shaping the informed decision making regarding a purchase of customers [41].…”
Section: Online Customer Reviewsmentioning
confidence: 99%
“…This difficulty is further amplified by the varying quality of and complexity in quality assessment on online courses, as well as the limited information and expertise of prospective learners in selecting courses [5]. To provide prospective learners with useful information and enable the sharing of course experience among learners, MOOC platforms commonly maintain a course review system that allows learners to post course reviews [6][7][8]. Learner reviews usually consist of a numeric rating and a short free-style textual comment to express learner opinions on courses.…”
Section: Introductionmentioning
confidence: 99%